2012
DOI: 10.1029/2012gl051994
|View full text |Cite
|
Sign up to set email alerts
|

Time‐history influence of global dust storms on the upper atmosphere at Mars

Abstract: [1] A recent survey of the Mars Global Surveyor (MGS) electron data for dayside photoelectron observations over regions of strong crustal fields revealed an unusual bimodal solar flux dependence. The elevated-flux population was associated with the timing of a large global dust storm in late 2001. The results of a systematic study parameterizing the photoelectron flux intensities against a solar flux proxy and MGS-observed atmospheric dust opacity are presented here. Instantaneous dust opacities were used as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…For the running average case, the time length is around 210 Earth days (approximately 110° Ls at Mars) for most bins. Notice that the time‐history length of the maximum value case is different from Liemohn et al [] (which said 210 Earth days for both cases). It is because the method of determining this window length is different between the two studies.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…For the running average case, the time length is around 210 Earth days (approximately 110° Ls at Mars) for most bins. Notice that the time‐history length of the maximum value case is different from Liemohn et al [] (which said 210 Earth days for both cases). It is because the method of determining this window length is different between the two studies.…”
Section: Resultscontrasting
confidence: 63%
“…Figure e is the local EUV proxy, i.e., F 10.7 cm solar flux at Mars multiplying a solar zenith angle‐dependent Chapman function [ Trantham et al , ], against time. The very low values during southern summer [ Liemohn et al , , Figure 1c], when the crustal fields were at LT 2 A.M. but partially illuminated due to the tilt of the planet, are also excluded as the partially illuminated magnetic loops very likely straddle the terminator, and therefore, these fluxes may behave differently. Figures b–d are time‐history dust opacity values against time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mars Global Surveyor (MGS) observations of the dayside photoelectrons revealed that dust storms can alter the atmosphere even up to the thermosphere for several months, thereby effecting the production, loss rates, and the flux of the photoelectrons in the upper ionosphere [cf. Liemohn et al ., ]. Large dust storms on Mars grow in the extratropics of southern hemisphere during spring/summer seasons [ Smith et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…We have no definitive answer to this puzzle and merely note two related recent observations. Liemohn et al (2012) found that periods of elevated dayside photoelectron flux at 400 km could be correlated with the average dust opacity over the preceding 7 months. Chaffin et al (2014) used MEX SPI-CAM ultraviolet observations to find that the hydrogen escape rate from Mars decreased by an order of magnitude over six months in 2007, coincident with the waning of a large dust storm in fall 2007 (Mars Year 28).…”
Section: Discussionmentioning
confidence: 92%